Teacher as a media figure in modern higher education: A competence-based approach - Poplavskyi, Mykhailo M. (Linguistics and Culture Review, 2021)
This study discusses the issues of evaluating a teacher as a media figure in modern higher education within the framework of a competence-based approach to perform this evaluation. The relevance of the subject matter is determined by the importance of media education problems in the development of modern pedagogy and the need to find effective ways to resolve the issues of evaluating the teacher’s role as a media figure considering their place in the system of modern higher education. The prospects for further research on this subject are determined by the importance of the proper development of the media educational space in a modern university, considering the acute need of society for a media-competent teacher, as well as the importance of a proper evaluation of the teacher’s role as a media figure in this process. The practical value of this study lies in the possibility of practical application of its results to develop an objective outlook on the evaluation of the teacher’s role and functions as a media figure in modern higher education.